a) X - 5X/2 = 1 1/2

b) R- R/2 = 1/3

C) 3m/2 - m-1/3= m/6

D)a+1/4 - m-1/3 = m/6

E) 3x - (x - x-3/3)=m/6

F)2x-(3. x+1/2)=-1

G)2x-3(x+1/2)= -1

H)X+1/2/3=0

I)x-x/2/3=1

j)t+t/3/5=0

Por favor pessoal me ajudem isso vale a metade da minha nota pra mim passa

1

Respostas

2013-08-28T18:06:10-03:00
F) 2x - (3. x + 1/2) = -1
2x - 3x - 1/2 = -1
4x - 6x - 1 / 2 = -2 / 2
-2x = -1
x = 1/2

G) 2x - 3(x + 1/2) = -1
2x - 3x - 3/2 = -1
4x - 6x - 3 / 2 = -2 / 2
-2x = - 2 + 3
x = -1/2

H) X + 1/2/3 = 0
x + (1/2 . 1/3) = 0
x + 1/6 = 0
x = -1/6

I) x - x/2/3 = 1
x - (x/2 . 1/3) = 1
x - x/6 = 1
6x - x / 6 = 6 / 6
5x = 6
x = 6/5

J) t + t/3/5 = 0
t + (t/3 . 1/5) = 0
t + t/15 = 0
15t + t / 15 = 0
16t = 0
t = 0

As outras já resolvi.
1 5 1